HYDROELECTRIC ROAD RAMP - Zarkeshev, A.; Csiszar, C. (Science and Transport Progress, 2019)
Purpose. The purpose of the study was to elaborate on a renewable source of energy using daily vehicles' traffic. The research question was how to produce electricity by using vehicle's kinetic energy and water-contained energy. In this paper «hydroelectric road ramp» is described as an auxiliary energy source which can be used in smart cities. Methodology. By conducting the literature review of adjacent methods and existing inventions, combining principles of work of these inventions, the system for producing electricity without destroying nature has been designed. Findings. Based on the supposition that 200 vehicles per hour pass over a ramp, the findings show that power generated by the system equals to 405,34 W. Considering the fact, that city roads function around the clock we can multiply the obtained result by 24 hours. Thus, we can accumulate a lot of electricity for efficient using in necessary goals. Even considering the fact that road capacity is different hour by hour, there is an opportunity to generate enough electricity for its conservation and further usage. Originality. From one side ‘hydroelectric road ramp’ is the system of generating electricity by using principles of work of conventional hydroelectric power station and pneumatic water sprayer, from the other side it is a speed breaker which may improve the safety conditions on the road. Practical value. The calculations we obtained led us to the theoretical conclusion that electricity getting from new source can be effectively used in the 'smart city' such as: powering street lights, traffic lights or serve as a complementary source of energy for e-mobiles charging points.